2013
DOI: 10.1002/macp.201300412
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Polyester–Polyolefin Copolymers by Combining Ring‐Opening Polymerization and Carbene Polymerization

Abstract: The ring‐opening polymerization (ROP) of a cyclic ester using alkyl acetate carbene (ROCOCH:) is generated from diazoacetate as organocatalyst under microwave irradiation, which enables the one‐pot preparation of copolymers of polyester and polyolefin. The chemical structure of the polymerized product is characterized by NMR, Fourier transformed infrared (FTIR), and UV–vis spectroscopy. The incorporation of the azo group into the obtained copolymer is determined by elemental analysis, which indicates that 1.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…1 The CP with a-carbonyl diazo compounds as carbene precursor has attracted much attention since Liu et al reported the rst instance of the polymerization of allyl diazoacetate by copper-mediated 2 and kinds of new polymers bearing an ester or aromatic group at every main chain carbon atom were synthesized from alkyl or aryl diazoacetate. 1,[3][4][5][6][7][8][9][10][11] The CP reaction of a-diazo carbonyl compounds has also been widely investigated in the past decade, which occurred usually in the presence of transition-metal (TM) complexes that mostly concerned the palladium (Pd) and rhodium (Rh) catalysts. 1,3 Ihara et al reported that Pd-catalysts incorporated with various ligands showed remarkably different polymers (oligomers), which clearly suggested that the variation of ligands had a major effect on the nature of the polymer and the kinetics of initiation step.…”
Section: Introductionmentioning
confidence: 99%
“…1 The CP with a-carbonyl diazo compounds as carbene precursor has attracted much attention since Liu et al reported the rst instance of the polymerization of allyl diazoacetate by copper-mediated 2 and kinds of new polymers bearing an ester or aromatic group at every main chain carbon atom were synthesized from alkyl or aryl diazoacetate. 1,[3][4][5][6][7][8][9][10][11] The CP reaction of a-diazo carbonyl compounds has also been widely investigated in the past decade, which occurred usually in the presence of transition-metal (TM) complexes that mostly concerned the palladium (Pd) and rhodium (Rh) catalysts. 1,3 Ihara et al reported that Pd-catalysts incorporated with various ligands showed remarkably different polymers (oligomers), which clearly suggested that the variation of ligands had a major effect on the nature of the polymer and the kinetics of initiation step.…”
Section: Introductionmentioning
confidence: 99%
“…ROP of cyclic monomers mediated by microwave irradiation is usually easy to conduct and a time‐saving, energy‐efficient process . In our previous work, one‐pot synthesis of poly(ester‐ co ‐olefin) by combining ROP and CP was conducted . Herein, we report the copolymerization using CP and ROP of cyclic monomers under microwave irradiation.…”
Section: Introductionmentioning
confidence: 98%
“…Studies on diazocarbonyl compounds have attracted increasing interest from many chemists since the copper‐mediated polymerization of allyldiazoacetate was first reported by Liu et al Subsequently, a series of carbine polymerizations of diazocarbonyl compounds catalyzed by palladium and rhodium with varieties of monomers were clearly demonstrated. Herein, copolymerizations of diazo compounds with alkenes constructed the propagating polymer chain with two carbon units, which conjugated C1 and C2 polymerization, yielding functionalized polyolefins, while traditional polymerization of CC bond substrates rarely obtained polymers with polar functional groups. Meanwhile, it also offers a convenient and green synthetic route for producing functional polymers.…”
Section: Introductionmentioning
confidence: 99%